2017
DOI: 10.1111/1756-2171.12207
|View full text |Cite
|
Sign up to set email alerts
|

The impact of consumer inattention on insurer pricing in the Medicare Part D program

Abstract: The Medicare Part D program relies on consumer choice to provide insurers with incentives to offer low‐priced, high‐quality pharmaceutical insurance plans. We demonstrate that consumers switch plans infrequently and search imperfectly. We estimate a model of consumer plan choice with inattentive consumers and show that high observed premiums are consistent with insurers profiting from consumer inertia. We estimate the reduction in steady state plan premiums if all consumers were attentive. An average consumer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 57 publications
3
103
0
Order By: Relevance
“…Ho et al. (), Polyakova (), and Heiss et al. () document the empirical prevalence of inertia among consumers and explore its implications for adverse selection and insurance company profits.…”
Section: Medicare Prescription Drug Insurance Marketsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ho et al. (), Polyakova (), and Heiss et al. () document the empirical prevalence of inertia among consumers and explore its implications for adverse selection and insurance company profits.…”
Section: Medicare Prescription Drug Insurance Marketsmentioning
confidence: 99%
“…() and Ho et al. (), we define an enrollment choice as active if either of the following statements is true: (i) The person is new to the market and must select a plan to become insured or (ii) the person switched to a new plan during open enrollment. If neither statement is true, then the decision maker took no action during open enrollment and was automatically reenrolled in the plan she chose last year—her default—in which case we define her choice as passive .…”
Section: Identifying Suspect and Nonsuspect Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Medicare context, the issue is complicated by the fact when an insurer reduces its bid, enrollees do not see a dollar reduction in their premium, but a 75 cent improvement in plan generosity. However, a fairly wide set of studies have found that consumers may not be highly price‐sensitive in choosing health plans, whether because they view plans as differentiated and value particular plan characteristics (Bundorf, Levin, and Mahoney ), or because behavioral factors such as choice inertia (Handel ), inattention (Ho, Hogan, and Scott Morton ), or optimization mistakes (Abaluck and Gruber ) lead to low price elasticity.…”
Section: Some Open Questionsmentioning
confidence: 99%
“…In the context of health insurance, the analysis is mostly focused on Medicare Part D. There is evidence that consumers are likely not optimizing effectively (Heiss, McFadden, Winter, Wuppermann, & Zhou, 2016), switch plans infrequently, and search imperfectly (Ho, Hogan, & Morton, 2017) and that switching probabilities decrease in the number of available health plans (Wuppermann, Bauhoff, & Grabka 2014), the time enrolled in Part (Ketcham, Lucarelli, & Powers, 2015). In Switzerland, for instance, health plans with midrange deductibles between CHF 500 and CHF 2,000 do not minimize individuals' total expenditure (i.e., premium plus co-payments) in most cases and are thus dominated by health plans with the lowest or highest deductible (CHF 300 and 2,500, respectively).…”
mentioning
confidence: 99%